Faktor Risiko Kelahiran Prematur di RSUD Dr. M. Soewandhi Surabaya pada Tahun 2017 - Bulqis Inas Sakinah; Dominicus Husada; Sulistiawati Sulistiawati (Majalah Kedokteran Indonesia, 2019)
Introduction: Preterm labor is one of the biggest direct cause of neonatal death and determined by various risk factors. Objective: To determine the effect of mother’s age, parity, preterm labor history, multiple pregnancy and pregnancy complications on the incidence of preterm labor. Method: Retrospective case-control method was conducted. Data were obtained from medical records of mothers who did labor in RSUD Dr. M. Soewandhi in 2017. Result: The analysis showed significant relationship between mother’s age (p=0,004), preterm labor history (p=0,006) and pregnancy complications (p less than 0,001) with the incidence of preterm labor. Based on multivariate analysis, mothers aged less than sign 20 and greater than sign dari 35 years old and those who had pregnancy complications were at risk of 3,510 (95% CI 1,481-8,230) and 5,203 (95% CI 2,248-12,040) times of having preterm labor.Conclusion: Maternal age and pregnancy complications were two contributing factors that increase the risk of preterm labor. These factors should be given special attention while assessing pregnancy to prevent preterm labor.